Buyang Huanwu Decoction alleviates cerebral ischemic injury through modulating caveolin-1-mediated mitochondrial quality control - Xu, Yaqian; Chen, Bowei; Yi, Jian; Tian, Fengming; Liu, Yingfei; Ouyang, Yin; Yuan, Chunyun; Liu, Baiyan (Frontiers in Pharmacology, 2023)
Mitochondrial quality control (MQC) is an important mechanism of neural repair after cerebral ischemia (CI). Recent studies have shown that caveolin-1 (Cav-1) is an important signaling molecule in the process of CI injury, but its mechanism of regulating MQC after CI is still unclear. Buyang Huanwu Decoction (BHD) is a classic traditional Chinese medicine formula that is often used to treat CI. Unfortunately, its mechanism of action is still obscure. In this study, we tested the hypothesis that BHD can regulate MQC through Cav-1 and exert an anti-cerebral ischemia injury effect. We used Cav-1 knockout mice and their homologous wild-type mice, replicated middle cerebral artery occlusion model and BHD intervention, neurobehavioral scores were used to evaluate neurological function, pathological detection of neuron damage, transmission electron microscopy and enzymology detection of mitochondrial damage, western blot and RT‒qPCR expression of MQC related molecules. The results showed that Cav-1 deletion aggravated the damage to neurological function, neurons, mitochondrial morphology and mitochondrial function after CI, aggravated the imbalance of mitochondrial dynamics, and inhibited mitophagy and biosynthesis. BHD can maintain MQC homeostasis after CI through Cav-1 and improve CI injury. In conclusion, Cav-1 can affect CI injury by regulating MQC, and this mechanism may be another target of BHD for anti-cerebral ischemia injury.